Hubungan Fleksibilitas Otot Hamstring Dengan Keseimbangan Dinamis Pada Lanjut Usia Wanita Di Posyandu Makamhaji Kartasura - Oktavia, Hana, Umi Budi Rahayu, S. Fis., M. Kes, Arif Pristianto, SSt.FT.,M.Fis (2016)
Background: flexibility is the deciding factor to the movement in humans. One of the muscles that play an important role in the daily activities is the hamstring muscles. The flexibility of hamstring muscles are muscles are very determined by length of hamstring muscles. When the hamstring muscles are shortened, the flexibility of the muscles is decrease. So, will affect the balance of muscles performance and can bring up annoyances of everyday activities, such as a change in the attitude of posture and walk activity. Objective: to know the relationship of the hamstring muscles flexibility with dynamic balance in the elderly women. Research methods: observational study with cross sectional analytic study designd aims to find out the relationship of muscle hamstring flexibility with dynamic balance in the elderly women, with a large sample of 80 people. Data analysis techniques using univariate tests with a frequency distribution table and bivariate test with chi-square test. Research result: the relationship between hamstring muscles flexibility with dynamic balance in the elderly women obtained the result of (p= 0,013 and IK 95%, so a significant relationship between the two variables. Conclucsion: there is relationship between the hamstring muscles flexibility and dynamic balance on the elderly women.